Identifying the Needs of Refugee and Asylum-Seeking Children in Thailand: A Focus on the Perspectives of Children - Thoresen, Paradee; Fielding, Angela; Gillieatt, Sue; Thoresen, Stian (Oxford University Press, 2016)
This research reports on the under-researched needs of urban refugee and asylum-seeking children living in precarious circumstances in Bangkok, Thailand. Further, it takes an unconventional approach and utilizes child-centred research methods to privilege the perspectives of children. It then compares children’s perspectives with those of adults who are their parents/guardians and key informants who are service providers and policy advocates. Qualitative research methods, including participant observation, semi-structured interviews and drawing with children, were employed in late 2014. This article reports remarkable findings on the similarities and differences between the perspectives of children and adults. The similarities and differences are contextualized in light of the supports and services available to improve the children’s wellbeing.